2021
DOI: 10.2196/preprints.28318
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Short-Video Apps as a Health Information Source for Chronic Obstructive Pulmonary Disease: Information Quality Assessment of TikTok Videos (Preprint)

Abstract: BACKGROUND Chronic obstructive pulmonary disease (COPD) has become one of the most critical public health problems worldwide. Because many COPD patients are using video-based social media to search for health information, there is an urgent need to assess the information quality of COPD videos on social media. Recently, the short-video app TikTok has demonstrated huge potential in disseminating health information and there are currently many COPD videos available on TikTok; however, the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Some evidences indicated that Tiktok had vast communication potential during the COVID-19 pandemic [8,23]. In addition, Bilibili and Tiktok contain numerous popular videos about diabetes, in ammatory bowel disease, obstructive pulmonary disease, liver cancer and other diseases, which have gained a plenty number of likes, comments and so on [11][12][13]24]. In our study, we found a similar trend in the abundance of videos related to thyroid nodules, capturing the interests of viewers.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Some evidences indicated that Tiktok had vast communication potential during the COVID-19 pandemic [8,23]. In addition, Bilibili and Tiktok contain numerous popular videos about diabetes, in ammatory bowel disease, obstructive pulmonary disease, liver cancer and other diseases, which have gained a plenty number of likes, comments and so on [11][12][13]24]. In our study, we found a similar trend in the abundance of videos related to thyroid nodules, capturing the interests of viewers.…”
Section: Discussionsupporting
confidence: 74%
“…The speci c scoring details for GQS are presented in Supplementary Table 3. The GQS and DISCERN score were chosen due to their widespread use in assessing information quality on various video-based platforms or diseases [12,19]. Two quali ed doctors specialized in thyroid disease scored the videos.…”
Section: Videos Assessmentsmentioning
confidence: 99%
See 2 more Smart Citations